Developmental Impairments in a Rat Model of Methyl Donor Deficiency: Effects of a Late Maternal Supplementation with Folic Acid - Geoffroy, Andréa (Int J Mol Sci, 2019)
Vitamins B9 (folate) and B12 act as methyl donors in the one-carbon metabolism which influences epigenetic mechanisms. We previously showed that an embryofetal deficiency of vitamins B9 and B12 in the rat increased brain expression of let-7a and miR-34a microRNAs involved in the developmental control of gene expression. This was reversed by the maternal supply with folic acid (3 mg/kg/day) during the last third of gestation, resulting in a significant reduction of associated birth defects. Since the postnatal brain is subject to intensive developmental processes, we tested whether further folate supplementation during lactation could bring additional benefits. Vitamin deficiency resulted in weaned pups (21 days) in growth retardation, delayed ossification, brain atrophy and cognitive deficits, along with unchanged brain level of let-7a and decreased expression of miR-34a and miR-23a. Whereas maternal folic acid supplementation helped restore the levels of affected microRNAs, it led to a reduction of structural and functional defects taking place during the perinatal/postnatal periods, such as learning/memory capacities. Our data suggest that a gestational B-vitamin deficiency could affect the temporal control of the microRNA regulation required for normal development. Moreover, they also point out that the continuation of folate supplementation after birth may help to ameliorate neurological symptoms commonly associated with developmental deficiencies in folate and B12.